2014
DOI: 10.1039/c4cp01864h
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation of Mo nanopowders through electroreduction of solid MoS2in molten KCl–NaCl

Abstract: Electrolysis of MoS2 to produce Mo nanopowders and elemental sulfur has been studied in an equimolar mixture of NaCl and KCl at 700 °C. The reduction mechanism was investigated by cyclic voltammetry (CV), potentiostatic and constant voltage electrolysis together with spectroscopic and scanning electron microscopic analyses. The reduction pathway was identified to be MoS2 → LxMoS2 (x ≤ 1, L = Na or K) → L3Mo6S8 and LMo3S3 → Mo, and the last step to format metallic Mo was found to be relatively slow in kinetics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Nonetheless, no anodic peaks were seen in the first cycle of sulfides (Figure 2b), demonstrating all the released S 2− had moved away from the cavity at the first scan. A high speed for removal of S 2− benefited from the high solubility of S 2− in NaCl‐KCl melt (∼39 mol/L in NaCl at 712 °C) [20] . Meanwhile, the reduction peaks could be hardly seen in the following two cycles of Sb 2 S 3 , [16] Cu 2 S (Figure 2c) and Sb 2 S 3 ‐Cu 2 S (Figure 2d), reflecting the rapid kinetics of electro‐desulfurization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, no anodic peaks were seen in the first cycle of sulfides (Figure 2b), demonstrating all the released S 2− had moved away from the cavity at the first scan. A high speed for removal of S 2− benefited from the high solubility of S 2− in NaCl‐KCl melt (∼39 mol/L in NaCl at 712 °C) [20] . Meanwhile, the reduction peaks could be hardly seen in the following two cycles of Sb 2 S 3 , [16] Cu 2 S (Figure 2c) and Sb 2 S 3 ‐Cu 2 S (Figure 2d), reflecting the rapid kinetics of electro‐desulfurization.…”
Section: Resultsmentioning
confidence: 99%
“…A high speed for removal of S 2À benefited from the high solubility of S 2À in NaCl-KCl melt (~39 mol/L in NaCl at 712 °C). [20] Meanwhile, the reduction peaks could be hardly seen in the following two cycles of Sb 2 S 3 , [16] Cu 2 S (Figure 2c) and Sb 2 S 3 -Cu 2 S (Figure 2d), reflecting the rapid kinetics of electrodesulfurization.…”
Section: Dg ¼ à Nefmentioning
confidence: 96%
“…However the formation of RS x and R x M y S z phases was often reported in these studies as intermediate phase during reduction. 69,12) This strongly suggests a contribution of R as the reductant in the melt. The authors examined the molten salt electrolysis of TiS 2 13,14) and V 3 S 4 15) under the concept of calciothermic reduction as based on OS process.…”
Section: Introductionmentioning
confidence: 99%
“…The fast supply of Ca to the reaction front is another important key for industrial application, as reported in OS process. 24) Another mechanism, FFC-Cambridge process, 1) requires ionization of sulfide and S 2¹ dissolution because the sulfide at the cathode should release S 2¹ to form the metal 612) via the lower sulfides, 7,12) and that S 2¹ diffuses out from the sulfides to the CaCl 2 melt. If we apply this mechanism to titanium sulfide, their proposal can be written as,…”
Section: Introductionmentioning
confidence: 99%
“…10,11) Previously, some studies have investigated the reduction of metal sul des such as MoS 2 , Cu 2 S, and CuFeS 2 by the electrolysis in molten salt. [12][13][14][15] These sul des can easily be re ned by the conventional route without electrolysis. However, vanadium sul de has a strong af nity with sulfur so that it is dif cult to remove sulfur by hydrogen.…”
Section: Introductionmentioning
confidence: 99%